Nutrigenética aplicada: dieta personalizada y formación académica para la práctica profesional - Coronado H., Marta (2011)
The aim of this paper is to focus on the new perspectives which are offered by the advent of genomics (nutrigenetic) and their potential on individual nutrition recommendations. Moreover, this article examines the influence of polymorphism on the response to dietary patterns which is the key player in the nutrigenetic field. It is clear that genetic variation influences nutritional requirements, therefore it will influence personalized nutrition recommendation. This paper also focuses on consumer population perspectives concerning nutrigenetics and examines the academic training of future health professionals.